Methotrexate induced erythema multiforme: a rare case report (BIRDEM Medical Journal, 2023)
Methotrexate is commonly used in the treatment of inflammatory disorders and malignancies. Although it is an effective therapeutic agent, it may have serious adverse effects in both therapeutic dose and overdose. Here, we report a case of a 54-year-old lady with polyarthritis, who was prescribed 2 tablets of methotrexate (10 mg) orally once a week. However, mistakenly the patient started taking the drug daily. After 12 days of starting methotrexate, she presented with widespread skin lesions, sore mouth and dysphagia. A diagnosis of methotrexate induced erythema multiforme was made. Laboratory investigations revealed pancytopenia. She was managed conservatively. Although rare, methotrexate overdose should be considered along with other possibilities in a patient with erythema multiforme. This case report also focuses on the rational use of drugs as well as the importance of good communication between health care professionals and patients.BIRDEM Med J 2023; 13(1): 52-55